ECOLOGICAL EDUCATION - GABRIELA GYONGY MIHUT (Challenges of the Knowledge Society)
While in most emerging and developing countries, the population has a lower ecological footprint in the developed countries have a larger footprint.There is also an alarming contrast between a person perception of her liability for damages to its environment and its actual size. These misconceptions may have their source in the absence of awareness of risks from climate change, culture or religion.The purpose of this study is to analyze the situation at the international and Romanian level and to draw attention on the necessity of un ecological education.